Analisis Penyebab Putusnya Wire Crane pada Kegiatan Bongkar Muat di Tanjung Pemancingan Anchorage di Kapal MV. Pacific Bulk - Rico Bayu Fanreza; Arleiny Arleiny; Teguh Pribadi; Elise Dwi Lestari (Pusat riset dan Inovasi Nasional, 2025)
The loading and unloading process involves moving goods from one place to another, often requiring specialized equipment such as a wire crane. In maritime operations, unexpected incidents like wire crane breakage can occur. Wire crane breakage refers to damage in the sling wire of a ship's crane, reducing its lifting capacity and causing the wire fibres to unravel. During sea-based fieldwork on the MV. Pacific Bulk, researchers observed a wire crane failure during loading and unloading operations, which caused delays and financial losses. This study aims to identify the causes of wire crane breakage on the MV. Pacific Bulk and examine its technical and operational impacts. Using a qualitative descriptive method and fishbone analysis for data interpretation, the study found several contributing factors: wire corrosion, crane age, lack of standard operating procedures (SOPs) for crane maintenance, insufficient crew, inadequate maintenance, lack of routine inspections, and challenging environmental conditions. The research also highlights the technical and operational consequences of such failures, including delays and economic loss. To address the issue, the study suggests implementing scheduled periodic inspections following SOPs, applying regular lubrication, and maintaining data records of the wire crane’s lifespan. These preventative measures aim to improve operational efficiency and avoid future wire crane failures.